Lignin-Degrading Enzymes of the Commercial Button Mushroom, Agaricus bisporus - Bonnen, Alice M. (1994)
Agaricus bisporus, grown under standard composting conditions, was evaluated for its ability to produce lignin-degrading peroxidases, which have been shown to have an integral role in lignin degradation by wood-rotting fungi. The activity of manganese peroxidase was monitored throughout the production cycle of the fungus, from the time of colonization of the compost through the development of fruit bodies. Characterization of the enzyme was done with a crude compost extract. Manganese peroxidase was found to have a pI of 3.5 and a pH optimum of 5.4 to 5.5, with maximal activity during the initial stages of fruiting (pin stage). The activity declined considerably with fruit body maturation (first break). This apparent developmentally regulated pattern parallels that observed for laccase activity and for degradation of radiolabeled lignin and synthetic lignins by A. bisporus. Lignin peroxidase activity was not detected in the compost extracts. The correlation between the activities of manganese peroxidase and laccase and the degradation of lignin in A. bisporus suggests significant roles for these two enzymes in lignin degradation by this fungus.